What Is the Role of AI in Orthopedic Surgery Planning? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Artificial intelligence (AI) is rapidly transforming various fields of medicine, and orthopedic surgery is no exception. The integration of AI into surgical ...
Keywords: AI in Surgery and Robotics; Orthopedic; Surgery; Planning; Artificial Intelligence; Machine Learning